Large area thermal light emission from autonomously formed suspended graphene arrays. (September 2018) - Park, Mina; Lee, Aram; Rho, Ho Kyun; Lee, Seoung-Ki; Bae, Sukang; Jeon, Dae-Young; Lee, Dong Su; Kim, Tae-Wook; Im, Yeon-Ho; Lee, Sang Hyun
Abstract: Since its discovery, the existence of graphene, a 2D extract of graphite, has been in the spotlight in the field of optoelectrical physics. Suspended graphene is potentially an ideal structure for utilizing intrinsic properties of the graphene by reducing the hindrance due to interaction with substrate. Here, an autonomous fabrication of suspended graphene is proposed where it only requires a single transfer which yields multiple arrays of micron-scale suspended graphenes all at once. Large area graphene sheets transferred onto a substrate of array-patterned 3D-electrodes easily tear into pieces due to the strain gradients induced by the step heights of the electrode patterns, and each torn graphene piece takes its position between individual electroplated Cu-microgap electrode pairs. With the absence of long-range scattering from randomly charged impurities in the substrate and the correspondingly enhanced carrier mobility of suspended graphene, our novel structure is demonstrated for the application of a visible light-emitting device. It is observed that the electrically driven thermal emission spectra spans the blue side of the visible band, which corresponds to a temperature of above 3000 K. The facile access to mass production of suspended graphene can bridge the current 2D materials research to the wide field of electronics and optoelectronics. Graphical abstract: Image 1